PENGARUH PENGGUNAAN CAMPURAN PUPUK ORGANIK DAN ANORGANIK TERHADAP PERTUMBUHAN ANAKAN SENGON (PARASERIANTHES FALCATARIA) - R Sudradjat; Sri Komarayati (Pusat Penelitian dan Pengembangan Hasil Hutan, 1992)
The purpose of this work is to study the effect of organic and anorganic fertilizer mixture to the growth of sengon (Paraserianthes falcataria) seedlings. The properties tested were height increment, dry weight and number of branches.The results show that the application of fertilizer and aerobic compost combination gave a highly significant effect on promoting plant height and dry weight of sengon seedlings as well as the number of branches, while the application of aerobic compost had no effect on branching,Combination of 50% compost and 5 gram chicken manure give the highest plant height of 28. 34 cm, while the lowest is in the treatment of 0.25 gram NPK, that is 1.48 cm. Combination of 40% compost and 5 gram chicken manure give the highest plant dry weight of 0.89 gram, while the lowest is in the NPK treatment.